ANALISIS KANDUNGAN NITRIT PADA SOSIS BERMEREK DAN TIDAK BERMEREK DI KOTA MEDAN 2016 - Suci Defayanti; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The sausages are defined as food made from ground meat and spiced and wrapped in a casing into a cylindrical shape is symmetrical. Nitrite as a preservative is safe to use, but even safe to consider the safety limit its use in food so as not to cause a negative impact on human health. Permenkes No. 116 / Menkes / Per / X / limit the maximum use of nitrite preservatives in processed meat products in the amount of 125mg / kg. Nitrite preservatives can lead to some effects such as nausea, vomiting, headache,  low blood pressure, and muscle weakness. The purpose of this study is to determine the levels of nitrite contained in sausage meat products sold in raw materials burger place in the city of Medan, and then compared with the maximum levels of nitrites permitted refers to Permenkes No. 1168 / Menkes / Per / X / 1999. Samples were six sausage products from four different places namely Transmart Carefourr, Brastagi Supermarket, Pondok Indah Fruit Market and Tanjung Rejo Market. Determination of nitrite levels carried by visible spectrophotometry using a color reagent N- (1-naphthyl) ethylene diamine dihydrochloride at a wavelength of 537 nm maximum. The identification results showed all samples were determined to contain nitrite. Nitrite levels were obtained respectively in the sausage is sample code P1 amounted to 62.4 mg / kg, P2 amounted to 1467.36 mg / kg, P3 amounted to 158.88 mg / kg, P4 amounted to 329.92 mg / kg, amounting to P5 121.12 mg / kg, and sample code P6 amounted to 37.6 mg / kg Three samples did not meet the requirements based Permenkes No. 1168 / Menkes / Per / X / 1999, were sample with code P2, P3 and P4. To BPOM and Health Department had to inform the regulations on the use of food additives and dangers of the used of food additives on health. Keywords: Sausage, Nitrite, Determination of Levels